Legal Protection Urgency for MSMEs Actors as well as Partnership Program which are Regulated according to Law Number 11 of 2020 on Job Creation - Nida, Salwa (Universitas Islam Negeri Walisongo Semarang, 2022)
The constitution (UUD 1945) gives recognition of human rights to develop themself and exists legal protection of the rights. This article attempts to provide a normative-juridical explanation about how Micro, Small, and Medium Enterprise (MSMEs) gets legal protection through omnibus law and government regulation supporting it. Law number 11 of 2020 about job creation, familiar with omnibus law, is formed to improve and to expand the economic sector. One of the omnibus law aims is to give ease of licensing to MSMEs to enrol the business activities. MSMEs are considered very helpful to create jobs, leading to the rising national economy. Therefore, MSMEs is given the opportunity to be a legal person and to be a private enterprise. The other protections of omnibus law for MSMEs are services of legal aid and legal protection in expanding the business activities by partnership programs with big enterprises. There are about 10 partnership programs among MSMEs and big enterprises. Looking from this form of written laws, this omnibus law is the part of legal protection for MSMEs, either business actors or business enterprises.Undang-Undang Dasar Tahun 1945 memberikan pengakuan terhadap hak warga negara untuk mengembangkan dirinya serta perlindungan hukum atas hak tersebut. Artikel ini berusaha memaparkan secara normatif-yuridis terkait bagaimana UMKM mendapat perlindungan hukum melalui UU Cipta Kerja serta peraturan pemerintah yang mendukungnya. Undang-Undang No 11 Tahun 2020 tentang Cipta Kerja atau yang dikenal dengan omnibus law dibentuk dengan tujuan untuk memperbaiki dan memperluas sektor ekonomi. Salah satunya ialah dengan memberikan kemudahan perizinan bagi UMKM dalam mendaftarkan kegiatan usahanya. UMKM dinilai sangat membantu terciptanya lapangan pekerjaan sehingga meningkatkan perekonomian negara. Oleh karena itu, UMKM juga diberikan peluang untuk berbadan hukum dan menjadi perseroan perorangan. Perlindungan lain yang diberikan dari undang-undang ini adalah adanya layanan bantuan hukum bagi UMKM dan perlindungan hukum dalam memperluas kegiatan usaha UMKM melalui program kemitraan, ada sekitar 10 program kemitraan UMKM Bersama usaha besar. Melihat dari bentuk aturannya yang tertulis, maka undang-undang cipta kerja ini adalah bagian dari perlindungan hukum bagi pelaku usaha dan badan usaha UMKM. Artikel ini berusaha memaparkan secara normatif-yuridis terkait bagaimana UMKM mendapat perlindungan hukum melalui UU Cipta Kerja serta peraturan pemerintah yang mendukungnya.